Identification of self-esteem levels in secondary school students according to: sex, grade an area of origin - Rojas Pedregosa, Pedro (IJERI: International Journal of Educational Research and Innovation, 2022)
The objective of this study is to show the level of self-esteem of secondary school students, both in urban and rural areas and according to gender and year group, in the province of Córdoba (Spain). The sample consists of 307 students from four secondary schools. The Garcia (1995) self-esteem evaluation questionnaire for secondary school students was used. The results show statistically significant discrepancies according to gender: for physical, general, intellectual, emotional self-esteem, relationships with others and on the independent scale of self-criticism. Depending on the year group, there are differences in physical and general self-esteem and the self-critical independence scale. On the other hand, significant correlations are observed (slight ones, between the students’ age and their general and physical self-esteem and the self-critical independence scale). These results are useful in terms of identifying specific aspects of self-esteem that could be fostered in the school environment.